Taniec śmierci na scenie kolegium jezuickiego w Kaliszu? - Kurek, Krzysztof; Wydra, Wiesław (Poznańskie Studia Polonistyczne. Seria Literacka, 2013)
The discussion was prompted by the discovery, made in Cathedral Library in Gniezno, of a notebook from early 18th century, with notes by a student of the Jesuit college in Kalisz. The authors have found in it a modified copy of a poem (Różnych stanów piękne grono [The Beautiful Gathering of Various Estates]) written on the famous late-17th-century painting, Taniec śmierci [The Dance of Death], displayed in the Franciscan monastery in Kraków. The authors propose a hypothesis that the copy of the poem was a script for a show staged in the college. The discussion is given in a wide cultural and theological context, presenting the danceof-death topos as reflection of the idea of vanitas. The article presents modes of concretization of the dance macabre image in European art from the 14th to 17th century, with particular attention paid to theatrical productions of the topos in popular shows and in Jesuit school theatrical productions.